Promising high-k dielectric permittivity of pyrochlore-type crystals of Nd2Hf2O7. Issue 3 (8th December 2014) - Chun, J.; Reuvekamp, P. G.; Chen, D.; Lin, C.; Kremer, R. K.
Abstract : We report on the properties of a Nd2 Hf2 O7 single crystal which is a promising high- k gate dielectric due to its high permittivity and band gap. Abstract : A single crystal of Nd2 Hf2 O7 was grown by the floating-zone technique. We have characterized its structural, dielectric, optical and thermal properties. At room temperature, the static dielectric constant amounts to ∼46. Ultraviolet absorption measurements indicate a direct band gap of ∼5 eV.